Effect of Pyrolysis Carbon Black from Waste Tire on the Mechanical Properties of SSBR/BR Blend. Issue 6 (28th March 2022) - Zhang, Guojie; Zhang, Yong; Wang, Shifeng; Jiang, Yang
Abstract: Pyrolysis carbon black (PCB) is a main product during the pyrolysis of waste tires. Using PCB to partially replace carbon black has drawn great attention. Herein, PCB is used to replace commercial carbon black N234 in a solution‐polymerized styrene‐butadiene rubber (SSBR)/butadiene rubber (BR)/silica compound used for tire treads. The influence of liquid polyisoprene (LIR) on the SSBR/BR/silica compound is studied. The scorch time of the compound is prolonged and the curing rate increases when N234 is partially replaced by PCB, and the processing performance of the compound is improved after the addition of LIR. As N234 is partially replaced by PCB, the addition of LIR can increase the tensile strength and elongation at break of SSBR/BR/silica vulcanizates, and improve their ageing resistance. When 50% N234 is replaced by PCB in the presence of LIR, the rolling resistance and wet grip of SSBR/BR/silica vulcanizate are improved, while the abrasion resistance slightly decreased. In the presence of liquid polyisoprene, PCB can be successfully used to partially replace common carbon black in tire rubber compounds without compromising properties. Abstract : Pyrolysis carbon black from waste tire is successfully used to replace commercial carbon black N234 in styrene‐butadiene rubber (SSBR) compounds used for tire tread. Modified liquid polyisoprene can improve the mechanical properties, aging resistance, and rolling resistance and wet grip of SSBR vulcanizates with N234 partially replaced by pyrolysis carbon black.